Enhancing antitumor immunity: the role of immune checkpoint inhibitors, anti-angiogenic therapy, and macrophage reprogramming - Zhang, Chong; Wang, Hua; Li, Xinying; Jiang, Yuxin; Sun, Guoping; Yu, Hanqing (Frontiers in Oncology, 2025)
Cancer treatment has long been hindered by the complexity of the tumor microenvironment (TME) and the mechanisms that tumors employ to evade immune detection. Recently, the combination of immune checkpoint inhibitors (ICIs) and anti-angiogenic therapies has emerged as a promising approach to improve cancer treatment outcomes. This review delves into the role of immunostimulatory molecules and ICIs in enhancing anti-tumor immunity, while also discussing the therapeutic potential of anti-angiogenic strategies in cancer. In particular, we highlight the critical role of endoplasmic reticulum (ER) stress in angiogenesis. Moreover, we explore the potential of macrophage reprogramming to bolster anti-tumor immunity, with a focus on restoring macrophage phagocytic function, modulating hypoxic tumor environments, and targeting cytokines and chemokines that shape immune responses. By examining the underlying mechanisms of combining ICIs with anti-angiogenic therapies, we also review recent clinical trials and discuss the potential of biomarkers to guide and predict treatment efficacy.